Aspirin Modulates Innate Inflammatory Response and Inhibits the Entry of Trypanosoma cruzi in Mouse Peritoneal Macrophages - Aparecida Donizette Malvezi; Rosiane Valeriano da Silva; Carolina Panis; Lucy Megumi Yamauchi; Maria Isabel Lovo-Martins; Nagela Ghabdan Zanluqui; Vera Lúcia Hideko Tatakihara; Luiz Vicente Rizzo; Waldiceu A. Verri; Marli Cardoso Martins-Pinge; Sueli Fumie Yamada-Ogatta; Phileno Pinge-Filho (Mediators of Inflammation)
The intracellular protozoan parasite Trypanosoma cruzi causes Chagas disease, a serious disorder that affects millions of people in Latin America. Cell invasion by T. cruzi and its intracellular replication are essential to the parasite’s life cycle and for the development of Chagas disease. Here, we present evidence suggesting the involvement of the host’s cyclooxygenase (COX) enzyme during T. cruzi invasion. Pharmacological antagonist for COX-1, aspirin (ASA), caused marked inhibition of T. cruzi infection when peritoneal macrophages were pretreated with ASA for 30 min at 37°C before inoculation. This inhibition was associated with increased production of IL-1β and nitric oxide (NO∙) by macrophages. The treatment of macrophages with either NOS inhibitors or prostaglandin E2 (PGE2) restored the invasive action of T. cruzi in macrophages previously treated with ASA. Lipoxin ALX-receptor antagonist Boc2 reversed the inhibitory effect of ASA on trypomastigote invasion. Our results indicate that PGE2, NO∙, and lipoxins are involved in the regulation of anti-T. cruzi activity by macrophages, providing a better understanding of the role of prostaglandins in innate inflammatory response to T. cruzi infection as well as adding a new perspective to specific immune interventions.